Influence of Vertical Load on the Lateral Response of Piles in Normally Consolidated and Over-Consolidated Clay: Centrifuge and Numerical Modelling - Liu, Tao; Lai, Yongqing; He, Ben; Lv, Na (Frontiers in Physics, 2022)
Although pile foundations are usually subjected to both lateral and vertical loads, there have been few studies on the pile response under the combined loadings. Moreover, those few studies led to inconsistent conclusions concerning the influence of vertical load on the lateral pile response. This study aims to investigate the effect of vertical load on the monotonic and cyclic lateral response of piles in normally consolidated (NC) and over-consolidated (OC) clay through a series of centrifuge tests. Three-dimensional finite element analyses using an advanced hypoplastic clay model were also performed to gain deep insight into the mechanism. It is revealed that after applying the vertical load and allowing the dissipation of the induced excess pore pressure, the lateral initial stiffness and ultimate capacity of the pile in the NC clay increased by 10.0% and 49.4%, respectively. However, in the OC clay, the application of the vertical load resulted in a 12.6% and 32.4% reduction in the lateral pile initial stiffness and ultimate capacity, respectively, showing a distinct response from that in the NC clay. The above-mentioned distinct influence of vertical load for piles can be attributed to the different evolutions of stress ratio (q/p’) of the soil around the pile in the NC and OC clay, which determines the soil mobilisable shear strength and consequently the lateral pile responses.